Educational Attainment and Neighbourhood Outcomes: Differences between Highly-Educated Natives and Non-Western Ethnic Minorities in the Netherlands - Elise de Vuijst; Maarten van Ham (Institute of Labor Economics (IZA), 2017)
In the Netherlands, obtaining a higher education increases the chance to move to a better neighbourhood for native Dutch adults who grew up in a deprived parental neighbourhood. For non-Western minorities, education does not have this positive effect on socio-spatial mobility. In this study we investigate potential explanations for these ethnic differences in the relationship between educational attainment and neighbourhood outcomes over time. We use longitudinal register data from the Netherlands to study a complete cohort of parental home leavers who attained a higher education by the end of the measurement period (1999 to 2012). We supplemented this data with information gathered in the WoON-survey. We examined differences in income trajectories for highly-educated native Dutch and non-Western ethnic minorities; investigated the strength of intergenerational transmission of income for both groups; and assessed individual neighbourhood experiences and contentment. We find that the highly-educated native Dutch in our subpopulation have a substantially higher average income over time, and a weaker association to the income of their parents compared to the non-Western ethnic minorities. Additionally, for ethnic minorities, our results show that the level of contentment with their neighbourhood is highest in deprived neighbourhoods compared to more affluent residential environments, and they more often reside in close proximity to their parents compared to the native Dutch, both suggesting an element of choice in neighbourhood selection.
Keywords: I30; J60; P46; R23; 330; neighbourhood histories; intergenerational transmission; income; education; ethnicity; longitudinal data